The Relationship Between Charge Nurses and Clinical Nurses' Perceptions of Patient Safety Culture and Leadership Practices - Ayşegül Yılmaz; Sergül Duygulu (Dokuz Eylul University, 2021)
Background: A patient safety culture needs to be developed for quality and safe care in health care institutions. Executive nurses having transformational leadership behavior have an important effect on establishing a patient safety culture in hospitals. Objectives: The aim of this study is to reveal transformational leadership practices of unit charge nurses from their own perspective and the perspective of staff nurses they work with, to determine the patient safety culture perceptions of unit charge nurses and staff nurses, and to examine the relationship between transformational leadership practices and patient safety culture. Methods: This descriptive, relationship-seeking and cross-sectional study was conducted between March and June 2014 in four hospitals in Konya province. The sample of the study consisted of 70 unit charge nurses and 357 staff nurses working with these unit charge nurses. Participation rate in the study is 84.5%. Data were collected by using the Demographic Data Form, Leadership Practices Inventory and Patient Safety Culture Hospital Questionnaire. Means, t test, percentages, standard deviation and Spearman's tests were used in the analysis of the data. Results: According to the evaluations of the unit charge nurses and staff nurses; it was found that the unit charge nurses' averages scores for prodding others into action, encouraging others and questioning the process sub-dimension and total leadership practice were significantly higher than those of the staff nurses. Patient Safety Culture perceptions of unit charge nurses are higher than service nurses. According to the findings obtained from the study, there is a positive relationship between nurses' transformational leadership practices and patient safety culture. Conclusion: In the study, it has been shown that there is a positive relationship between nurses' transformational leadership practices and patient safety culture. In order to create a positive patient safety culture in the units of charge nurses, it is necessary to develop the unit charge nurses' transformational leadership practices.